Upper Limit of Coefficient of Variation for Improving Efficiency in Sugarcane Field Experiments in India - Rajesh Kumar; A.D. Pathak; A.K. Sharma (Journal of the Indian Society of Agricultural Statistics, 2025)
Coefficient of variation (CV) is used to measure the heterogeneity of the experimental field in the context of agricultural research including sugarcane experiments. Smaller the CV value of cane yield, higher is the reliability of the experiment. In all the zones of All India Coordinated Research Project on Sugarcane - AICRP(S), upper limit of CV for cane yield is higher for early varietal trials in comparison to the mid to late varietal trials of sugarcane in India. Similar trend was also found for upper limit of CV for sucrose (%). Upper limit of CV (%) for cane yield was found highest in Peninsular zone as around 10% in early varietal trial followed by North central Zone. It is also observed as lowest in North West Zone, which is around 8.5 % both for early and mid-late varietal trials. Same trend was also observed for sucrose, which around 3% at 1%, 5% and 10% level of significance. Overall for all the trial of cane yield, it is estimated as 9% for cane yield in the country at all the three level of significance. For plant crop, it is estimated as 9% at all level of significance. For ratoon crop, it is estimated as 10% at all level of significance.